Factors and focuses in the strategic decisions of sporting organisations: empirical evidence in sports associations. (16th February 2009) - Soares, Jorge; Correia, Abel
The aim of this study is to gain insights into the factors and focuses guiding the strategic decision-taking process in the sports associations of the Autonomous Region of Madeira (Portugal). Based on a qualitative research methodology, three techniques of gathering data are used in triangulation: analysis of the contents of documents; observation of the board meetings; and qualitative interviews with presidents. Our findings suggest that the associations should adopt strategies to revitalise and develop the regional competitions and the quality of the representative teams, in addition to fostering active and systematic cooperation with the directors and coaches of the regional clubs, with the objective of creating projects to further develop the sport. The paper's limitations are considered and recommendations are made.